A Diagnostic Nomogram Based on 18F-FDG PET/CT for Bone Metastasis of Gastric Cancer - Wu, Chunhui; Lin, Xiaoping; Li, Zhoulei; Chen, Zhifeng; Xie, Wenhui; Zhang, Xiangsong; Wang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2021)
Purpose To develop an effective diagnostic model for bone metastasis of gastric cancer by combining 18F-FDG PET/CT and clinical data. Materials and Methods A total of 212 gastric cancer patients with abnormal bone imaging scans based on 18F-FDG PET/CT were retrospectively enrolled between September 2009 and March 2020. Risk factors for bone metastasis in gastric cancer were identified by multivariate logistic regression analysis and used to create a nomogram. The performance of the nomogram was evaluated by using receiver operating characteristic curves and calibration plots. Results The diagnostic power of the binary logistic regression model incorporating bone-related symptoms, anemia, the SUVmax of bone lesions, bone changes, the location of bone lesions, ALP, LDH, CEA, and CA19-9 was significantly higher than that of the model using only clinical factors (P=0.008). The diagnostic model for bone metastasis in gastric cancer using a combination of clinical and imaging data showed an appropriate goodness of fit according to a calibration test (P=0.294) and good discriminating ability (AUC=0.925). Conclusions The diagnostic model combined with the 18F-FDG PET/CT findings and clinical data showed a better diagnosis performance for bone metastasis in gastric cancer than the other studied models. Compared with the model using clinical factors alone, the additional 18F-FDG PET/CT findings could improve the diagnostic efficacy of identifying bone metastases in gastric cancer.